Learn OS X Lion - Meyers, Scott; Lee, Mike (Apress : Imprint: Apress, 2011)
You're smart and savvy, but you're also busy. This comprehensive guide to Apple's latest version of OS X, Lion, gives you everything you need to know to live a happy, productive Mac life. Learn OS X Lion will have you up and connected right away. With a minimum of overhead and a maximum of useful information, you'll cover a lot of ground in the time it takes other books to get you plugged in. If this isn't your first experience with OS X, skip right to the "What's New in Lion" sections. You may also find yourself using this book as a quick refresher course or a way to learn new Mac skills you've never tried before.